Monitoring Kinerja Mesin Tetas Otomatis Berbasis Internet Of Things - Nirwana, Hafsah; Raharjo, Muh Fajri; Pangerang, Fitriaty; T, Zein; syahrir, syahrir (Jurnal Teknologi Elekterika, 2022)
This study aims to destroy an automatic egg incubator, where the performance parameters to be monitored are the temperature and humidity of the incubator. The monitoring system uses the Internet of Things (IoT) application. The egg incubator utilizes the lamp's heat to maintain the room temperature's stability. Utilizing the DHT11 sensor, the temperature data will be processed on the Wemos d1 microcontroller, which is then sent to the internet wirelessly. The temperature and humidity data results will be read in real-time using IoT with the Blynk platform, which can also be accessed using a smartphone. The results of this study apply IoT technology to the monitoring system for measuring conditions of the incubator temperature and humidity parameter values. All device modules will be packaged into embedded systems integrated with environmentally friendly IoT innovation rules and support the technological era of the industrial revolution 4.0. The results of measurements at the incubator's location and the monitoring using the Blynk application are relatively the same, and the success rate of hatching eggs reaches 74% of the total eggs put into the incubator